"En Christō" as Pauline Argument against Synoptic Demonology: Implications for the Church in Africa. (July 2020) - Onyenali, Rowland
There is no doubt that exorcism of demons is a central feature in the synoptic presentation of the works of the earthly Jesus. This central issue among the synoptic writers is absent in the gospel according to John and in the writings of St Paul. This article argues that a plausible explanation of this absence is that the issue of demonic possession was not important to the communities founded among the Hellenistic Christians of Asia Minor. Instead of presenting the encounters between Jesus and the demons, Paul presents the incorporation into Christ as a definitive victory over the forces of sin and evil. The Christian incorporated "in Christ" has won the battle over the devil. Understanding and implementing this Pauline vision among African Christians is a better missionary approach than the current chasing after demons that characterize contemporary Christianity in Africa.